Sidearm effect in (thio)urea/alkoxide‐mediated ring‐opening polymerization of cyclic esters. Issue 6 (13th January 2021) - Zhu, Ningning; Behzadi, Shabnam; Si, Guifu; Tan, Chen
Abstract: Thiourea and urea catalysts have received much attention in the field of ring‐opening polymerization. In the (thio)urea/alkoxide catalytic system, sidearm groups can influence the catalytic performance of the organocatalyst moiety. In this work, a series of (thio)ureas bearing 2‐, 3‐ and 4‐pyridyl moieties were designed and synthesized. The (thio)ureas bearing a 2‐pyridyl group exhibited much higher catalytic activities than the (thio)ureas bearing 3‐ or 4‐pyridyl groups, suggesting a sidearm effect. Both crystal data and computational studies indicated that 2‐pyridyl can form an intramolecular hydrogen bond with the NH moiety, resulting in a Brønsted base/Lewis acid bifunctional catalytic system. Furthermore, the catalyst was stimuli‐responsive in Lewis acid/base‐modulated ring‐opening polymerization. Coordination between the Lewis acid BEt3 and the catalyst was found to terminate the polymerization. Subsequently, the coordinated species was cleaved using the Lewis base bicyclo[2.2.2]‐1, 4‐diazaoctane, resulting in the reactivation of the catalyst. © 2020 Society of Chemical Industry Abstract : A 2‐pyridyl group can improve the catalytic activity of (thio)urea/alkoxide systems in ring‐opening polymerization of lactones, suggesting a sidearm effect.